2022
DOI: 10.1158/1078-0432.ccr-22-0470
|View full text |Cite
|
Sign up to set email alerts
|

Malic Enzyme 1 Absence in Synovial Sarcoma Shifts Antioxidant System Dependence and Increases Sensitivity to Ferroptosis Induction with ACXT-3102

Abstract: Purpose: To investigate the metabolism of SS and elucidate the effect of malic enzyme 1 absence on SS redox homeostasis. Experimental Design: ME1 expression was measured in SS clinical samples, SS cell lines, and tumors from a SS mouse model. The effect of ME1 absence on glucose metabolism was evaluated utilizing Seahorse assays, metabolomics, and C13tracings. The impact of ME1 absence on SS redox homeostasis was evaluated by metabolomics, cell death assays with inhibitors of antioxidant systems, and measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…45,46,52 ME1 has also been identified as a ferroptosis defense protein in hepatic ischemia/reperfusion injury and synovial sarcoma. 60,61 Our work establishes a novel connection between PK and ME1 as well as their roles in ferroptosis in pancreatic cancer. Additionally, our study shows that inhibition of ME1 provides a route to promote ferroptosis and circumvent PDAC metabolic defense strategies for surviving low cystine conditions.…”
Section: Discussionmentioning
confidence: 68%
“…45,46,52 ME1 has also been identified as a ferroptosis defense protein in hepatic ischemia/reperfusion injury and synovial sarcoma. 60,61 Our work establishes a novel connection between PK and ME1 as well as their roles in ferroptosis in pancreatic cancer. Additionally, our study shows that inhibition of ME1 provides a route to promote ferroptosis and circumvent PDAC metabolic defense strategies for surviving low cystine conditions.…”
Section: Discussionmentioning
confidence: 68%
“…S7 F ), suggesting that MYC and ME2 affect glutamine oxidation but not reductive carboxylation in Jurkat cells. Furthermore, we performed 1,2- 13 C glucose–tracing experiment ( 26 , 31 ). Consistent with the results for glucose consumption, neither MYC knockdown nor ME2 overexpression affected glucose metabolism through glycolysis or pentose phosphate pathway in Jurkat cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that p53 inhibits ME2 including ME1 transcription, and reciprocally, ME1 and ME2 inhibit p53 activation through different mechanisms ( 21 ). A recent study reported an important role for ME1 in the regulation of redox homeostasis in synovial sarcoma ( 26 ). Here, we report that ME2 is a target of MYC and plays a critical role in MYC-driven T cell lymphomagenesis.…”
mentioning
confidence: 99%
“…[31,32] A recent study by Brashears et al showed that synovial sarcoma lacks ME1 expression which drives decrease in intracellular NADPH and GSH levels. [33,34] Interestingly, ME1 deficiency render synovial sarcoma cells sensitive to erastin-induced ferroptosis, but resistant to GSH depletion-induced cell death. Reprogramming of redox homeostasis in the context of ME1 absence may explain how these cells adapt to be less dependent on GSH.…”
Section: Discussionmentioning
confidence: 99%